Analisis Pengendalian Kecepatan DC Motor Berbasis Buck-Boost Konverter - Dwi Ajiatmo; Imam Robandi (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2018)
Buck Boost converter controls the use of efficient and economical low and medium power applications, another advantage is its simple design. Very fast response speed, low harmonic distortion components, and high power factor. In this paper, simulation control of the Buck-Boost DC Motor is presented using PSIM software. The results of the analysis and simulation with the PSIM program can be summarized as follows: In open loop dc motor speed, stable in 4.181 seconds and DC motor speed -2.499 rpm. In a closed loop controlled condition, the dc motor speed is stable at 2,308 seconds and the DC motor speed is 6,702 rpm.